Tinjauan Hukum Batalnya Suatu Perkawinan Terhadap Perjanjian Kredit Bank - Mohammad Zamroni (Faculty of Law Hang Tuah University, 2017)
The main function of the bank is to collect funds from the public in the form of deposits, and channel them to the public in the form of credit facilities. However, because the funds used as credit facilities are public funds, then giving credit must be in accordance with the precautionary principle. One of the application of the precautionary principle is to make a credit contract. Credit contract are not only carried out by banks with companies, but also between banks and individual debitor. If an individual debitor is married and does not have a marriage agreement, the husband and wife are generally involved in a credit contract. This is done in addition to guaranteeing loan repayments, also related to guarantees that are generally in the form of property. Basically marriage ties still have the potential to be canceled. So that there will be legal consequences when the marriage is canceled. This study focuses on analyzing the legal consequences of the credit contract made by banks with an individual debitor whose marriages are canceled by the Court.